Leveraging Information and Communication Technology for Enhancing Students' Learning and Development of Scientific Works - Ulfah, Ulfah; Angela, Angela; Marzuki, Abdul Gafur; M, Elisabet; Baguilat, Ivan D. (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2025)
This study explores how integrating ICT into education can significantly improve students' learning experiences and foster the creation of scientific works. ICT tools, offer students enhanced access to information, promote critical thinking, and support the development of research and scientific writing skills. By incorporating ICT, educators can provide more interactive, personalized, and effective learning environments, ultimately enriching the academic and research capabilities of students. This study aims to explain how students in SMA Negeri 1 Torue learn to design scientific work using information and communication technology. This research is descriptive-qualitative in nature. The researchers used purposive sampling to collect the samples. The research subjects were 36 people, including one language teacher and 35 students. Observation, interviews, questionnaires, and documentation are data collection methods. Data reduction, data presentation, and conclusions are the three stages of data analysis. Based on observations, interviews, and documentation of Indonesian language teachers, it is evident that teachers are capable of adapting their approaches, media, and materials. This allows researchers to conclude that the use of information and communication technology in teaching students to design scientific work in class XI IPS 1 SMA Negeri 1 Torue is adequate.